Fine-tuning of regulatory T cell function: the role of calcium signals and naive regulatory T cells for regulatory T cell deficiency in multiple sclerosis - Schwarz, Alexander; Schumacher, Marijana; Pfaff, Daniel; Schumacher, Kai; Jarius, Sven; Balint, Bettina; Wiendl, Heinz; Haas, Jürgen; Wildemann, Brigitte (The journal of immunology, 2013)
The suppressor function of regulatory T cells (Tregs) is impaired in multiple sclerosis (MS), but the mechanisms underlying this deficiency are not fully understood. As Tregs counteract the sustained elevation of intracellular calcium, which is indispensable for full activation of conventional T cells (Tcons), we hypothesized that interference with this pathway might prompt MS-related Treg dysfunction. Using single-cell live imaging, we observed that Tregs rapidly reduce Ca2+ influx and downstream signals in Tcons upon cell contact, yet differ in their potency to efficiently suppress several target cells at the same time. Strikingly, individual Tregs harboring a CD4+CD25+FOXP3+CD45RA+ naive phenotype suppressed significantly more adjacent Tcons than did CD4+CD25+FOXP3+CD45RA− memory Tregs. Some constituents even completely failed to dampen Tcon Ca2+ influx and were contained exclusively in the memory subset. In accordance with their more powerful suppressive performance, the Ca2+ signature was considerably enhanced in naive Tregs in response to TCR triggering, compared with the memory counterparts. MS Tregs displayed a significantly diminished suppression of mean Ca2+ influx in the sum of individual Tcons recorded. This reduced inhibitory activity was closely linked to decreased numbers of individual Tcons becoming suppressed by adjacent Tregs and, in turn, correlated with a marked reduction of naive subtypes and concomitant expansion of nonsuppressive memory phenotypes. We conclude that the superior achievement of naive Tregs is pivotal in maintaining Treg efficiency. As a consequence, MS Tregs become defective because they lack naive subtypes and are disproportionately enriched in memory cells that have lost their inherent downregulatory activity.